Transforming Leadership, Effective Communication, And Patient Safety Culture: The Role Of Trust Among Hospital X East Jakarta Nurses - Heru Agusman; Duta Liana; Nofierni Nofierni (Publikasi Indonesia, 2023)
The importance of leadership and communication styles in upholding a safety culture in a health service. This research aims to analyse the influence of transformational leadership effective communication on patient safety culture with trust as mediation in nursing personnel in general hospital X. This study used a questionnaire involving 98 respondents with a cross-sectional quantitative research design using Structural Equation Modeling (SEM) with Smart Partial Least Square (PLS) software. The results of the study found that transformational leadership has a significant effect on patient safety culture, then effective communication has a significant effect on patient safety culture. Where the highest dimension of transformational leadership is inspirational motivation (89.9%), the highest dimension of effective communication is context (86.8%), the highest dimension in patient safety culture is a non-punitive response to error incidents (79.6%), while the highest dimension of trust is integrity (85.5%). The research concludes that transformational leadership and effective communication exert influence on trust-mediated patient safety culture